Nystartande av nötköttsproduktion med och utan bidrag - Krijger, Rolf (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
Many dairy farms doesn't keep their bull calves and cross cow calves, they sell them to breeders instead of raising them their self. It should be possible for the dairy farmers to do it them self's. There is also a possibility to bread one calf from the cross heifers. The purpose of the investigation was to see if there is any economic possibility to breed beef cattle. I have used the same sample farm trough the hole study, because it would be easier to fallow the study. I have made some calculating on four different raising models, I have calculated without subsidies. There is also calculations white subsidies to check how big the difference is. In the results it clearly shows that raising fattening bulls gave the best gross margin. When you compare the results with and without subsidies it clearly shows that it is impossible to raise beef cattle without subsidies.